PENGEMBANGAN SISTEM INFORMASI TRACKING OUTBOUND MENGGUNAKAN PENDEKATAN DESIGN SCIENCE RESEARCH - Felix, Felix Togap Rosario; Tambotoh, Johan (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2024)
Information systems for companies can be an important step because information systems play a vital role in managing, storing, processing, and accessing information efficiently. Researchers conducted research at PT Saleslab, a company that focuses on digital advertising. In 2022, PT Saleslab launched its own product called Nubiko, which is currently a baby cream product. PT Saleslab has an internal website that provides a central place for storing documents, company policies, guidelines, and other important information. However, PT Saleslab faces a problem in managing outbound product data because there is no outbound package tracking menu. The company still uses the manual method by inputting data on packages coming out of the warehouse using Microsoft Excel. Every product that is going out is scanned and inputted into Microsoft Excel, then submitted to the expedition, which is considered ineffective.This research uses a qualitative method with a Design Science Research (DSR) approach to develop an Outbound Tracking information system. The focus is to develop a website with innovation, ideas, ways of working, technical capabilities, analysis, design, implementation, and utilization of information systems as the main solution.